Paraphacosomoides Balthasar, 1968, a junior synonym of Lepanus Balthasar, 1966 (Coleoptera: Scarabaeidae: Scarabaeinae), with redescription of Lepanus curvipes (Balthasar, 1966) - Gunter, Nicole L.; Génier, François; Weir, Thomas A. (Zootaxa, 2025)
The monotypic genus Paraphacosomoides Balthasar, 1968 (Coleoptera: Scarabaeidae: Scarabaeinae) is treated as a junior synonym of the genus Lepanus Balthasar, 1966, and Lepanus curvipes (Balthasar, 1966), new combination is proposed for Paraphacosomoides curvipes (Balthasar, 1966). The invalid genus-group names Phacosomoides Balthasar, 1966 and Pseudophacosoma Paulian, 1975 are also placed in synonymy with Lepanus. Morphological evidence supports this synonymy and the tentative placement of Lepanus curvipes in the Lepanus villosus species group.